THE USE MICROCONTROLLERS FOR IMPROVEMENT OF FUNCTIONS OF DEVICES AND SYSTEMS (Modern information system and technologies, 2018)
This article discusses the relevance of using microcontrollers to improve the functions of devices and systems. The use of microcontrollers contributed to the transition from obsolete microcircuits to large integrated circuits, which are used to develop various computing devices. Keywords: microcontroller, power consumption, process environment, microprocessor, watchdog timer, register, timer